Development and characterization of Elaeis oleifera microsatellite markers - Noorhariza Mohd Zaki,; Ismanizan Ismail,; Rozana Rosli, (Universiti Kebangsaan Malaysia, 2010)
Ten Elaeis oleifera microsatellite markers were developed and characterised from 1500 sequences of the E. oleifera genomic library. The markers were utilised to assess the genetic diversity of E. oleifera germplasm collections from four South American countries (Colombia, Costa Rica, Panama and Honduras). The number of alleles per-locus varied from 2 to 11 and the observed and expected heterozygosity ranged from 0.0685 to 0.9853 and 0.1393 to 0.8216 respectively. Majority of the markers showed transferability to Elaeis guineensis while two markers showed transferability across Arecaceae taxa. These E. oleifera microsatellite markers are expected to become useful tools to determine the population structure and conservation of E. oleifera populations.